Florida Solid and Hazardous Waste Regulation Handbook: Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS, 2004)
The Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA) was enacted in 1980, and later amended by the Superfund Amendments and Reauthorization Act (SARA) in 1986. CERCLA empowers EPA to investigate and cleanup abandoned sites contaminated by hazardous substances and provides a trust fund for that purpose. CERCLA extends liability for site pollution to several classes of potential defendants at once. It is a powerful measure for forcing responsible parties to contribute to the costs of cleanup. This is EDIS document FE445, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.